Pengujian Black Box pada Aplikasi Desktop Penjualan Elektronik Menggunakan Metode Equivalence Partitioning - Susanto, Joko; Biqirrosyad, Biqirrosyad; Junaidi, Muhamad Mardian; Sudrajat, Yuliyandri; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Software testing requires validation to determine whether it meets the goals and specifications or not. If the validation process is not good, it can result in data being stored that is not good too, for example the login process becomes an error. Of course this will hamper using the application. So that the quality of validation must be improved until it is accurate. The testing phase must be carried out on applications that are designed in such a way that quality software is obtained. In this study we used Blackbox testing with the Equivalence Partitioning method. Namely by dividing or solving the program in the form of an input domain to the data class so that test cases can be obtained. We think this method is quite relevant for testing electronic sales applications. This research includes determining application functionality, designing test scenarios, determining the data to be tested, determining input which can be numerical values, value ranges, Boolean conditions according to the database structure that has been created, testing experiments, documentation of research results and drawing conclusions. The conclusion of this test is that this software is running well. But we realize that this test is not perfect due to the limited sample form. We hope that this application can be used according to user needs.